Interest Rate Channel and Real Economy in Nigeria: A Bayesian Vector Autoregression Approach - Osundina, Kemisola Christianah; Tella, Sheriffdeen A.; Adesoye, Bolaji A. (International Journal of Economics and Financial Issues, 2018)
This study examined the dynamic response of real economy to interest rate shocks using Bayesian vector autoregression model with Minnesota/Litterman prior criterion. Impulse Response Functions showed that all the variables were consistent with the theory apart from investment whose response was counter intuitive. Forecast Error Variance Decomposition confirmed theoretical interactions between Monetary Policy Rate through interest rate and inflation. Interest rate channel under this framework is effective to bring the economy to stability by suppressing inflation rate and bring it to normalcy in Nigeria with adverse effect on growth rate of Gross Domestic Product due to necessary and policy conflicts. Keywords: Minnesota/Litterman Prior, Bayesian. JEL Classifications: C11, C58